Biology and Reproductive Behaviour of Apanteles taragamae Viereck (Hymenoptera: Braconidae), a Larval Parasitoid of Diaphania indica Saunders (Lepidoptera: Crambidae) - Nurul Novianti Puspitaningtyas; Damayanti Buchori; Ihsan Nurkomar (Universitas Gadjah Mada, 2019)
Apanteles taragamae (Hymenoptera: Braconidae) is a larval parasitoid of Diaphania indica (Saunders) (Lepidoptera: Crambidae), a minor pest of Cucurbitaceae crop. The aim of this study was to determine the behavior and biology of A. taragamae. The study was conducted under laboratory conditions by exposing 930 larvae of D. indica to be parasitized by 11 adult female parasitoid of A. taragamae (1 day old), which have been mated 24 hours prior to expose. Each female was exposed to 15 larvae/day until they died. The parameters used to measure the biology of A. taragamae were fecundity, longevity, and parasitism. Results showed that the longevity of adult females was 5.64 days, the parasitism was 96%, the number of egg laid was 76.40/day, the total number of eggs laid was 611.18, and potential fecundity was 752.73 egg.